Patellofemoral joint biomechanics in the females with anterior knee pain applying full weight bearing kinematic MRI - Brazaitis, Andrius; Tamošiūnas, Algirdas; Tutkuvienė, Janina (Acta medica Lituanica, 2015)
Purpose. The aim of the study was to evaluate biomechanics of the patellofemoral joint using full weight bearing kinematic MRI. We postulated that females with unilateral PFP might have greater medial femoral rotation in comparrison to the contralateral knee, also greater lateral patella tilt and displacement. Methods. Forty four females aged 20–40 years with unilateral PFP were included in the study. The kinematic MRI examination was performed with a 1.5 T MRI unit. Full-weight bearing was used. Sagittal and axial images of the patellofemoral joint were acquired with a transmit-receive surface body coil. The study parameters, i. e. bisect offset, patella tilt angle, medial femoral rotation, patellar rotation at 0, 10, 20, 30, 40, 50° of flexion, were measured for both knees. Results. Statistically significant changes were confirmed for greater bisect offset at all angles of flexion. The patella tilt angle increased steadily throughout full extension, but there was no significant difference in the tilt angle at 50° flexion. Greater medial femoral rotation was observed at all degrees of flexion, while patellar rotation showed no difference. Conclusions. Our study has confirmed the growing body of literature, theorizing that the primary cause of PFP pain is altered femur dynamics under relatively stable patella.